Konsep Pendapatan Negara dalam Pemikiran Al-Mawardi dan Relevansinya bagi Keuangan Publik : The Concept of State Revenue in Al-Mawardi’s Thought and Its Relevance to Modern Public - Muhamad Afif Sholahudin; Mega Silvia; Yadi Janwari; Dedah Jubaedah (Litera Academica Publishing, 2026)
This article aims to analyze the concept of state revenue sources according to Imam Al-Mawardi and to examine its relevance within the context of modern state financial systems. Using a qualitative approach and library research, the study highlights that Al-Mawardi not only classifies types of revenue such as zakat, kharaj, jizyah, ghanimah, and emergency taxation (dharibah), but also emphasizes the principles of justice, proportionality, and public welfare (maslahah) in managing state finances. The findings indicate that the ethical values embedded in Al-Mawardi’s thought can be adapted to modern fiscal systems, particularly in terms of fiscal transparency, the protection of vulnerable groups, and accountability in the use of public funds. Although the structure of the state has evolved, fundamental values such as equitable distribution and public spending oriented toward the common good remain relevant for strengthening the legitimacy of state fiscal policies. Therefore, Al-Mawardi’s thought offers an important normative foundation for fiscal reform oriented toward welfare and social stability.